If it's not what You are looking for type in the equation solver your own equation and let us solve it.
14 + 6m -2 - 3m = 5m + 8
We simplify the equation to the form, which is simple to understand
14+6m-2-3m=5m+8
We move all terms containing m to the left and all other terms to the right.
+6m-3m-5m=+8-14+2
We simplify left and right side of the equation.
-2m=-4
We divide both sides of the equation by -2 to get m.
m=2
| 5x^2-10x+6y^2+36y+60=0 | | 5w^2=35w | | 12m-2m+3+4m=31 | | 12-2m+3+4m=31 | | 9v^2+9v-40=0 | | 6+8m+8=12m+2+4 | | 6+8m=12m+2+4 | | 8(m+4)(2m-1)= | | 9x+4x=0.9-1.4 | | 3M+15=5m+9 | | 5M+40=100 | | 100=5M+40 | | 151=7x-6(-3x+4) | | 2x-3.4=x-3.6 | | 2xy=x^6+y^6 | | 57.6=240(0.03)t | | 3x-13+4x-24=180 | | 1half(6x-8)=41 | | 3x-13=4x-24 | | 4x+2[4-2(x+2)]=2x-1 | | 4(m-4)=12 | | 18.8=2(3.14)r | | 22=2l+2(7) | | Y=x^5-1x^3-6x | | 9y=-45x+45 | | -y^2+9y-9=0 | | 2x+10=20x-20 | | 5m*5m+27m+34=0 | | x=2y+2 | | 4y^2+16y+18=0 | | 3x+3=105 | | 6x+10=70-4x |